Oil prices and fundamentals - Spector, K; Long, D; Horsnell, P (Oxford Institute for Energy Studies, 2005)
Katherine Spector analyses the market and its players; David Long sees this as the end of an era; Paul Horsnell thinks we are moving to a sustainable long-term price level.